229k views
1 vote
y varies jointly as a and b and inversely as the square root of c y=96 when a=8 b=6 c=16 find y when a=7 b=5 c=25

User Ehsan Msz
by
6.2k points

2 Answers

5 votes

y = 56

The initial statement is y varies as
(ab)/(√(c) )

To convert to an equation multiply by k the constant of variation

y =
(kab)/(√(c) )

y = 96 when a = 8 , b = 6 , c = 16

y =
(kab)/(√(c) )

hence k =
(y√(c) )/(ab)

=
(96√(16) )/(8 x 6) =
(96 x 4)/(8 x 6) = 8

Thus y =
(8ab)/(√(c) )

given a = 7 , b = 5 , c = 25 then

y =
(8 x 7 x 5)/(√(25) ) = 8 × 7 = 56




User Cbrandolino
by
5.5k points
4 votes


\bf \qquad \qquad \textit{compound proportional variation} \\\\ \begin{array}{llll} \textit{\underline{y} varies directly with \underline{x}}\\ \textit{and inversely with \underline{z}} \end{array}\implies y=\cfrac{kx}{z}\impliedby \begin{array}{llll} k=constant\ of\\ \qquad variation \end{array} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \stackrel{\textit{\underline{y} varies jointly as \underline{a} and \underline{b} and inversely as }√(c)}{y=\cfrac{kab}{√(c)}}



\bf \textit{we also know that } \begin{cases} y=96\\ a=8\\ b=6\\ c=16 \end{cases}\implies 96=\cfrac{k(8)(6)}{√(16)}\implies 96=\cfrac{48k}{4} \\\\\\ \cfrac{96\cdot 4}{48}\implies 8=k\qquad therefore\qquad \boxed{y=\cfrac{8ab}{√(c)}} \\\\\\ \textit{when } \begin{cases} a=7\\ b=5\\ c=25 \end{cases}\textit{ what is \underline{y}?}\implies y=\cfrac{8(7)(5)}{√(25)}\implies y=\cfrac{8(7)(5)}{5}\implies y=56

User Creaktive
by
6.2k points